Math for the pharmacy technician : - Egler, Lynn M. (McGraw Hill Higher Education, 2010)
Recognizing the enormous need for well-trained Pharmacy Technicians as well as the serious need to decrease medication errors, Math for Pharmacy Technicians: Concepts and Calculations was developed. This textbook is organized from simple to complex and walks the student through the necessary information to pass the math portion of the PTCB exam. The text includes Pharmacy Technician-specific information that is non-threatening and helps the student learn to safely practice as a Pharmacy Technician. This text is organized into 11 chapters, along with a pretest and a comprehensive evaluation or posttest.